Health and illness in multicultural societies 1 - Papadopoulos, Irena (Culturally Competent Compassion, 2018)
This chapter focuses on the Papadopoulos, Tilki and Taylor model of cultural competence. It begins by discussing some of the key concepts of the model before introducing the four main domains/constructs of the model, which are: (a) cultural awareness; (b) cultural knowledge; (c) cultural sensitivity; and (d) cultural competence. Using a case study, the reader is guided through the application of the model and is invited to reflect on the rationale of actions needed for culturally competent care.